2006
DOI: 10.1111/j.1365-2109.2005.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential of mixed culture of genetically improved farmed tilapia (Oreochromis niloticus) and freshwater giant prawn (Macrobrachium rosenbergii) in periphyton-based systems

Abstract: The production performance of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) and freshwater prawn (Macrobrachium rosenbergii) in periphyton‐based systems were studied in farmers' ponds at Mymensingh, Bangladesh. Fifteen ponds (200–300 m2 area and 1.0–1.5 m in depth) were used to compare five stocking ratios in triplicate: 100% GIFT, 75% GIFT plus 25% prawn, 50% GIFT plus 50% prawn, 25% GIFT plus 75% prawn and 100% prawn. Ponds were stocked at a total density of 20 000 GIFT and/or prawn ha−1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 15 publications
6
51
4
1
Order By: Relevance
“…The mean survival rate of prawn in the present study was significantly higher in treatment R 0 (63.6 ± 1.1 %). The overall survival of prawn (50 to 64%) in the present experiment was more or less similar to the reported values in earthen ponds: 62% (Kumar et al, 2000), 52 to 55% (Mazid and Mahmud, 1994) and 57 to 66% (Uddin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The mean survival rate of prawn in the present study was significantly higher in treatment R 0 (63.6 ± 1.1 %). The overall survival of prawn (50 to 64%) in the present experiment was more or less similar to the reported values in earthen ponds: 62% (Kumar et al, 2000), 52 to 55% (Mazid and Mahmud, 1994) and 57 to 66% (Uddin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…As prawn grew its increased grazing pressure led to reduced periphyton biomass. Uddin et al (2006) reported that freshwater prawns may feed selectively on periphyton. It may have picked preferentially on animal portion and detrital aggregates rather than picking up the mixed biomass.…”
Section: Abundance Of Plankton and Benthic Macroinvertebratesmentioning
confidence: 99%
“…Prawn (Macrobrachium rosenbergii) polyculture has a potentially higher net return than prawn monoculture (Rouse and Stickney, 1982). Culture of prawn with fish also improves the ecological balance of the pond water, preventing the formation of massive algal blooms (Cohen et al, 1983;Uddin et al, 2006). M rosenbergii is a benthophagic omnivore an excellent species for polyculture along with tilapia (Alam et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it can be positively presumed that the culture of freshwater prawn for export market and tilapia in the same pond for household consumption may be an innovative option for fish farmers. Contrariwise, tilapia may exhibit negative impact on prawn survival that may hamper total production (Garcia-Perez et al, 2000;Uddin et al, 2006). Therefore, we compared the growth performance of GIFT and Chitralada in freshwater prawn culture system with a view to finding better performed strain, and simultaneously, we evaluated the effect of tilapia addition on prawn production performance.…”
Section: Introductionmentioning
confidence: 99%